Optimal Stationary Contracts under One-Sided Enforcement and Persistent Adverse Selection - Martimort, David; Simons, Aggey (Université d'Ottawa | University of Ottawa, 2026)
We characterize the optimal contract within the class of stationary mechanisms in a repeated buyer-seller relationship with persistent adverse selection and one-sided limited enforcement. A prepaid seller may breach after receiving the current transfer and terminate the relationship upon paying an enforceable penalty. In this stationary benchmark, the enforcement problem collapses to a bound on the transfer targeted to the most efficient type. This yields a three-regime characterization. With strong enforcement, the repeated static second-best contract is feasible. With weak (intermediate) enforcement, the top transfer is capped, inducing bunching among efficient types and additional downward distortions. With very weak enforcement, public penalties alone cannot sustain compliance, and the principal must leave strictly positive continuation rents, including for the least efficient type. We interpret the associated distortion as a virtual enforcement cost.
Keywords: Adverse selection; Limited enforcement; Relational contracts; Contract breach